Water Use Quality Situation over 10 Years (2010 to 2019) of Hospitals under the Ministry of Public Health, Thailand - Peeratoranit T. (2023)
This study aimed to investigate the situation of hospital water use quality and determined concern parameters contributing to health risk factor. A total of 15,560 water use samples from hospitals in all regions of Thailand between 2010 to 2019 were sampled and analyzed. Inferential statistics were employed to determine significant differences and relationships among water quality parameters. Hospital water use came from various sources. The probability of water use without treatment involved quality parameters not meeting the standard criteria than those treated water around 1.8-9.3 times. Chemical water quality parameters always remained under the standard requirement of pH (9.5%) and turbidity (5.6%). The majority of problems involved microbial indicators; total coliform bacteria (43.9%) and fecal coliform bacteria (33.2%). Water parameters related to exceeded total and fecal coliform bacteria standards included turbidity, nitrate, chloride and pH levels. The highest explicit turbidity relationship of occurrence probability exceeded the quality standards with total and fecal coliform bacteria 3.7 and 4.3 fold, respectively. Onsite hospital water treatment is needed to ensure safe conditions. The significant chemical parameters can be used as a rapid tool to estimate the situation of microbial indicators. Constant and frequent monitoring of water quality should be implemented for all stakeholders.